Leading Directions of Tourism Development in Ural Region - KSENOFONTOVA, Tatyana Yurievna; TARKHANOVA, Natalya Petrovna; KOSHELEVA, Tatyana Nikolaevna; VORONOV, Alexander Alexandrovich; LUCHANINOV, Roman Sergeevich (Journal of Environmental Management and Tourism; Vol 12 No 8 (2021): JEMT, Volume XII, Issue 8(56), Winter 2021, 2021)
Changing the priorities of tourists results in a search for new directions, routes, and diversification of tourist offer. Moreover, different categories of tourists need different tourism products. Undoubtedly, there is a demand for recreation with a focus on active leisure. It can be adventure and environmental tourism. Demand for these areas shows steady growth. To increase inbound tourist flow, it is necessary to find destinations that can attract foreign tourists. The Ural region can be one of such territories. Environment, a significant number of specially protected natural areasand high transport accessibility are factors of attractiveness. The main locations that can attract tourists are national and natural parks: Yugyd-Va, Deer Streams, Bazhov places, Chusovaya River, Taganay, Zyuratkul (Russia). The formats of the planned tours are very diverse - from fishing and hunting to hiking, skiing and rafting tours of various complexity. Duration of travel from 3 to 14 days.The objects of environmental interest are stone outliers, rock formations, picturesque landscapes, caves, the opportunity to get acquainted with the unique culture of local nationalities and cultural and historical sights.The main issues of tourism development are connected with the lack of information on objects, including in a foreign language, and complex logistics in organizing tours in certain territories.